Travelling Salesman Problem Analysis with Complete Enumeration Method, Branch & Bound and Greedy Heuristic - Ifham Azizi Surya Syafiin; Sarah Nur Fatimah; Muchammad Fauzi (Eduvest - Journal of Universal Studies, 2021)
PT XYZ as the best and largest Bed Sheet Set company in Indonesia with products such as Bed Covers, Bed Sheets, Pillowcases, Bolsters and Blankets. The Traveling Salesman Problem (TSP) is a problem faced in finding the best route to visit shops that sell products from PT BIG. A visit to the shop is carried out on the condition that each city can only be visited once except the city of origin. The algorithms applied in this TSP problem include the Complete Enumeration, Branch & Bound and Greedy Heuristic methods.